Historical institutional differences and entrepreneurship: The case of socialist legacy in Vietnam - Christian Fisch; Michael Wyrwich; Thi Lanh Nguyen; Jörn Hendrich Block (Friedrich Schiller University Jena, 2020)
We study the case of Vietnam to assess the long-lasting role of institutional and historical legacy on entrepreneurial outcomes. In particular, we investigate the detrimental effect of socialist institutions on entrepreneurship. Vietnam offers a unique quasi-experimental setting because the country was divided into the socialist North and the nonsocialist South for a relatively short period of two decades. After re-unification the South adopted the institutional framework conditions of the North. To assess the relationship between socialist history and entrepreneurship in this unique setting, we survey more than 3,000 North and South Vietnamese individuals more than four decades after the re-unification of the country. We find that North Vietnamese respondents have lower entrepreneurship intention, are less likely to select into entrepreneurship education programs, and are less willing to engage in business takeover. These patterns indicate the persistence of a long-lasting influence of historical differences in institutional framework conditions on entrepreneurship. The long-run effect of socialism on entrepreneurship is apparently deeper than previously discovered in the prominent case of Germany, where differences in institutional treatment lasted for much longer and ended more recently.
Keywords: D02; L26; M13; P30; 330; Socialism; Vietnam; entrepreneurship intention; entrepreneurship education; takeover vs new venture startup